Gastric Emphysema in a Critically Ill Patient Successfully Treated without Surgery - Hiromi Ihoriya; Tetsuya Yumoto; Masaya Iwamuro; Noritomo Fujisaki; Takaaki Osako; Hiromichi Naito; Atsunori Nakao (Case Reports in Critical Care)
Gastric emphysema is a relatively rare clinical entity caused by injury to the gastric mucosa. A 62-year-old Japanese male with a history of heavy alcohol consumption and smoking was admitted to the emergency intensive care unit due to severe hypercapnic respiratory acidosis. His body mass index was only 12.6. Ten days after initiation of enteral feeding, he complained of abdominal pain. Computed tomography revealed intraluminal air in the distended gastric wall. Esophagogastroduodenoscopy showed diffuse edema, redness, and erosion throughout the stomach. Based on the findings of narrow angle and short distance of the aorta-superior mesenteric artery, the patient was diagnosed with gastric emphysema associated with superior mesenteric artery syndrome. He was successfully managed nonoperatively with treatments including intravenous antibiotics, gastric decompression, and bowel rest. Physicians should be aware of this unusual condition in such critically ill patients complaining of abdominal pain and needing close monitoring and observation to exclude gastric necrosis or perforation.